(A Study on Preservation of Pineapple Slices in Sugar Solution) - Endah Djubaedah Jusuf; Toni Sugandar; A. Basrah Enie (Warta Industri Hasil Pertanian, 1989)
Preservation of pineapple slices in sugar solution has been conducted. Chemical preservative used was sodium benzoic. The concentration of sugar (=Sucrose) used were 0% and 65%, while those of sodium benzoic were 0 and 0.15%. Plastic bags were used as packaging material using vacuum and non-vacuum sealing in plastic bag. The shelf life of this product was five days at room temperature.